(untitled) (Ameghiniana, 2013)
A description is provided for Wolfestheria smekali gen. and sp. nov., a new member of the family Fushunograptidae, from the “Estancia La Sin Rumbo” locality in the Puesto Almada Member of the Cañadón Asfalto Formation. Assignment to the family Fushunograptidae is supported by evidence from detailed scanning electron microscope studies of this species. An assessment of the complex carapace ornamentation is also provided, as W. smekali exhibits an array of ornamentations that cover the entire carapace surface. These consist of irregular, thick radial lirae with numerous thin cross-bars on the dorsal middle-upper third of the carapace, changing to straight, thick radial lirae with fewer cross-bars restricted to the upper half of the growth band in the ventral third of the carapace, with the interspaces between the radial lirae wider than the lirae themselves, and with the radial lirae terminating in the upper part of the growth bands, where they then enlarge to form a triangular shape upon contact with the following growth line. These characteristics allow us to compare W. smekali with the eosestheriid genera Yanjiestheria Chen and AbrestheriaWang, as well as with the other fushunograptids from the Upper Jurassic to Lower Cretaceous of China such as Cratostracus Huang and QinghaiestheriaWang. W. smekali is also comparable to fushunograptids and related forms from the Jurassic system of Argentina. The occurrence of W. smekali correlates biostratigraphically with the “Eosestheriopsis dianzhongensis fauna” of China, as well as with other Jurassic faunas from Africa and Europe. This correlation supports a Late Jurassic age for these fossiliferous assemblages (Puesto Almada Member, Cañadón Asfalto Formation) from the province of Chubut, Argentina. Resumen. PRIMER REGISTRO DE LA FAMILIA FUSHUNOGRAPTIDAE (“CONCHOSTRACA”, SPINICAUDATA) DE LA FORMACIÓN CAÑADÓN ASFALTO (JURÁSICO SUPERIOR), PATAGONIA ARGENTINA. Se describe Wolfestheria smekali gen. y sp. nov., Familia Fushunograptidae de la Formación Cañadón Asfalto, Miembro Puesto Almada, localidad “Estancia La Sin Rumbo”. Los estudios detallados a través de la microscopía electrónica de barrido de la nueva especie, brindaron características que permitió asignarla a dicha familia. También aportaron información sobre la compleja ornamentación que cubre la totalidad del caparazón, compuesta por gruesas estrías radiales con numerosas y delgadas barras transversales en el tercio medio-dorsal del caparazón, cambiando a gruesas y rectas estrías radiales con unas pocas barras transversales en el tercio ventral del caparazón, estas barras están restringidas a la mitad superior de las bandas de crecimiento, los espacios entre las estrías radiales son más anchos que las estrías mismas, éstas no alcanzan la parte superior de las bandas de crecimiento y en su base se ensanchan hasta formar una estructura de forma triangular. Estas características permitieron comparar el nuevo taxon con los géneros de eosestherideos Yanjiestheria Chen y Abrestheria Wang, y también con otros fushunograptideos, como Cratostracus Huang y QinghaiestheriaWang del Jurásico Superior y Cretácico Inferior de China. También, la nueva especie fue comparada con los fushunograptideos y formas relacionadas del Sistema Jurásico de la Argentina. Desde el punto de vista bioestratigráfico, W. smekali permitió comparar nuestra asociación con la “fauna de Eosestheriopsis dianzhongensis” y con otras faunas Jurásicas de África y Europa que apoyan la edad jurásica tardía para el Miembro Puesto Almada de la Formación Cañadón Asfalto (Provincia del Chubut, Argentina).